From alluvial fan to playa: an Upper Jurassic ephemeral fluvial system, Neuquén Basin, Argentina - Spalletti, Luis Antonio (2005)
The Upper Jurassic fill of the back-arc Neuquén Basin includes a lowstand wedge known as the Tordillo Formation. The studied deposits crop out along a N-S to oriented belt that runs parallel to the Andean magmatic arc. They are limited to the south by the east-west oriented positive structure of the Huincul arch formed as a result of Upper Jurassic tectonic inversion. The Tordillo deposits were formed in an and fluvial-dominated system characterised by systematic downstream changes in architectural style. A gravelly and sandy bedload fluvial system is recognised in the southern upstream sector. The reduced thickness and the coarse grain size suggest steep gradients, excess of bedload supply and a low subsidence rate. Thicker and finer-grained deposits prevail to the north and northeast. They were formed under arid conditions in a wadi-sand flat-playa fluvial system. This distal facies association indicates increased accommodation owing to high rates of subsidence relative to coarse siliciclastic sedimentation rates. These low-gradient deposits are characterised by cyclic alternations of mud-dominated and sand-dominated packages interpreted as high- and low-accommodation systems tracts. The overall fining upward stacking pattern of the Tordillo Formation suggests a change towards higher accommodation rates. This is accompanied by frequent development of soil horizons and darker primary and reworked pyroclastic deposits. These attributes indicate a stronger explosive volcanic activity associated with increased precipitation and high water table emplacement towards the end of the Tordillo lowstand wedge. © 2005 International Association for Gondwana Research, Japan.